Preparation and Property of Xylan/Poly(Methacrylic Acid) Semi-Interpenetrating Network Hydrogel - Xiao-Feng Sun; Yang Feng; Xiaodi Shi; Yaxiong Wang (International Journal of Polymer Science)
Xylan/poly(methacrylic acid) semi-interpenetrating network hydrogels were synthesized, and these hydrogels were fabricated using various ratios of xylan and methacrylic acid and cross-linked by N,N′-methylenebisacrylamide. The chemical structure and morphology of the prepared hydrogels were characterized by FT-IR spectroscopy and SEM analysis. The porous structure of the prepared hydrogels was found, and the interconnected porous channels increased when the content of xylan was increased in the hydrogels. The hydrogels presented excellent pH sensitivity and swelling reversibility. The dynamic swelling kinetics were also studied, and all obtained results indicated that the prepared xylan/poly(methacrylic acid) semi-IPN hydrogel could be used in biomedical fields, especially for drug release.